2022
DOI: 10.1186/s12882-022-02856-x
|View full text |Cite
|
Sign up to set email alerts
|

The stay strong app as a self-management tool for first nations people with chronic kidney disease: a qualitative study

Abstract: Background The high burden of chronic kidney disease in First Nations peoples requires urgent attention. Empowering people to self-manage their own condition is key, along with promotion of traditional knowledge and empowerment of First Nations communities. This study explores the potential of a culturally responsive tool, already found to have high acceptability and feasibility among First Nations people, to support self-management for First Nations people with kidney failure. The Stay Strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Participants' mean (SD) age was 33.9 (8.7) years. They had been using methamphetamine from a median age of 21 years (IQR 18-28 years) and had used methamphetamine on a median (IQR) of 20 [13][14][15][16][17][18][19][20][21][22][23][24][25] days in the past 4 weeks. Eighty-two per cent smoked tobacco (92% of these, daily).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants' mean (SD) age was 33.9 (8.7) years. They had been using methamphetamine from a median age of 21 years (IQR 18-28 years) and had used methamphetamine on a median (IQR) of 20 [13][14][15][16][17][18][19][20][21][22][23][24][25] days in the past 4 weeks. Eighty-two per cent smoked tobacco (92% of these, daily).…”
Section: Resultsmentioning
confidence: 99%
“…[9] In a context where demand for specialist alcohol and other drug (AOD) treatment across urban, rural and remote settings in Australia is not met by available services, much of the burden for providing care to people who use methamphetamine falls to primary health care services. [11] The AOD assessment [17,18], psychosocial assessment and care planning [19], and suicide prevention.…”
Section: Original Manuscriptmentioning
confidence: 99%
“…In a third study, an app was used by clients with a practitioner present, and technical difficulties were reported with an Android emulator to enable compatibility with Windows [ 40 ]. The fourth study used the same app as the previous study [ 40 ] with a different population; thus, it was also used by clients with a practitioner present, but no technical difficulties were reported [ 39 ]. Although many studies evaluating mHealth apps have reported technical challenges, it seems that using a web-based application may have resulted in more users experiencing technical challenges and a more substantial challenge of not being able to log in or save the application.…”
Section: Discussionmentioning
confidence: 99%
“…The women also commented that it did not "look" like an application and that it was slow. Other application trials with Aboriginal and Torres Strait Islander people have largely used Android or iOS apps [15,[38][39][40][41]. Of these studies, 1 was unable to collect use data for 34% (21/61) of the participants reporting flat batteries, connectivity issues, and other problems [41].…”
Section: Principal Findingsmentioning
confidence: 99%
“…The development of kidney care apps, on the other hand, can provide trustworthy content directly to individuals and provide a secure platform to engage with clinicians. Two Australian studies have developed specific apps; Nagel et al [36] implemented a self-management app for First Nations people in Australia, finding that the majority of users were able to engage with the technology to set a wellbeing goal. A health literacy app for people with kidney failure requiring dialysis has been developed with evaluation of it in progress [37].…”
Section: Technologymentioning
confidence: 99%